Copula-based dynamic conditional correlation multiplicative error processes - Taras Bodnar; Nikolaus Hautsch (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
We introduce a copula-based dynamic model for multivariate processes of (non-negative) high-frequency trading variables revealing time-varying conditional variances and correlations. Modeling the variables' conditional mean processes using a multiplicative error model we map the resulting residuals into a Gaussian domain using a Gaussian copula. Based on high-frequency volatility, cumulative trading volumes, trade counts and market depth of various stocks traded at the NYSE, we show that the proposed copula-based transformation is supported by the data and allows disentangling (multivariate) dynamics in higher order moments. To capture the latter, we propose a DCC-GARCH specification. We suggest estimating the model by composite maximum likelihood which is sufficiently flexible to be applicable in high dimensions. Strong empirical evidence for time-varying conditional (co-)variances in trading processes supports the usefulness of the approach. Taking these higher-order dynamics explicitly into account significantly improves the goodness-of-fit of the multiplicative error model and allows capturing time-varying liquidity risks.
Keywords: C32; C58; C46; 330; multiplicative error model; trading processes; copula; DCC-GARCH; liquidity risk; Handelsvolumen der Börse; Marktliquidität; Wertpapierhandel; Kopula (Mathematik); Multivariate Analyse; Theorie; USA